Temperature-Programmed Capillary Electrophoresis for Detection of DNA Point Mutations. (November 1996) - Gelfi, Cecilia; Cremonesi, Laura; Ferrari, Maurizio; Righetti, Pier Giorgio
A method for unambiguous determination of point mutations in genomic DNA, based on electrophoresis in thin capillaries, is reported here. The method is based on the principle of temperature gradient gel electrophoresis (TGGE), a variant of denaturing gradient gel electrophoresis (DGGE), and exploits the differential melting of mutant and wild-type PCR-amplified DNA fragments during electrophoresis through a temperature gradient. Unlike TGGE, where the temperature gradient exists along the separation space, the denaturing temperature gradient in the fused-silica capillaries is time-programmed, so as to reach the melting points ( Tm s) of all species under analysis prior to electrophoretic transport past the detector window. The DNA fragments are injected in a capillary maintained (by combined chemical and thermal means) just below the expected Tm values. The temperature increment applied is typically minute (1°–1.5°C) and the sweep speed is rather shallow (e.g., 0.05°C/min). Additionally, the denaturing thermal gradient is not controlled externally, but generated internally by Joule heat produced by voltage ramps. Point mutants are fully resolved into a spectrum of four bands, with a dynamic range extending from 45°C (low melters) up to 70°C for high melters. The present method can thus be universally applied to any type of point mutation.